Nature of the interaction of paramagnetic atoms (A=N-4,P-4,O-3,S-3) with pi systems and C-60: A theoretical investigation of A center dot center dot center dot C6H6 and endohedral fullerenes A@C-60 - Clark, Timothy; et al. (Journal of Chemical Physics, 2002)
The nature of the interaction of paramagnetic atoms A (=N-4,P-4,O-3,S-3) with pi systems and C-60 in the A...C6H6 complexes and endohedral fullerenes (A@C-60) has been investigated employing second-order Moller-Plesset perturbation level of theory and density functional theory calculations. The coupled cluster theory with single and double excitations, and with perturbed triplet excitations have also been carried out for the A...C6H6 complexes. The calculated geometries indicate that the paramagnetic N and P atoms lie on the C-6 axis of benzene in the A...C6H6 complex and at the center of the C-60 cage in A@C-60. On the other hand, the O and S atoms are slightly shifted towards the C-C bond of benzene in the A...C6H6 complex. A comparison of the calculated binding energies (BEs) of these paramagnetic complexes and the corresponding rare gas complexes like He...C6H6 and He@C-60 indicate that the BEs of the former are much larger than those of the latter. For both the rare gas and paramagnetic atom complexes dispersive interactions dominate the BEs. The energy barriers of the penetration of the O atom through a [6,6] bond are lower than the penetration of the helium atom and higher than the penetration of a N atom. (C) 2002 American Institute of Physics.